Mitigation of toxic alexandrium tamiyavanichii using chitosan-silica composite = Mitigasi alexandrium tamiyavanichii bertoksik menggunakan komposit kitosan-silika - Iqbal, Anwar; Ahmad, Najwa; Mohammad Noor, Normawaty; Wilson, Lee D.; Ibrahim, Nur Hanisah (Malaysian Analytical Society, 2019)
The harmful algal bloom (HABs) phenomena affects human health, ecosystems, fishing, and tourism industries. In a single occasion, the loss due to HABs can reach thousands of Ringgit Malaysia. In this study, a chitosan-silica composite (RHA-CHi) was synthesized via sol-gel technique for the mitigation of Alexandrium tamiyavanichii, a toxic HAB species isolated from Malaysian waters. Rice husk ash silica was used as the silica precursor in the composite synthesis. The FT-IR spectroscopy suggests that the chitosan was covalently bonded with the surface silanol groups. Light microscope analysis showed that the algal cells were stuck on the surface of the composite and underwent lysis. The incorporation of chitosan decreased the surface negative charge of the silica, hence, increasing the electrostatic attraction between the cells and RHA-Chi. The removal efficiency of A. tamiyavanichii was 75% using 0.1 mg/mL of RHA-Chi in 2 hours, increasing to 85% after 24 hours. Reduced removal efficiency (16%) was observed using silica alone. The findings show that the chitosan-silica composite has high potential to be used in the mitigation of A. tamiyavanichii.